Impact of self-perceptions, social norms, and social capital on nascent entrepreneurs: a comparative analysis by level of economic development in Latin American countries - Barrera Verdugo, Gustavo Alfonso. (Springer, 2021)
The impact of individual psychological and social conditions on participation in entrepreneurship has been widely studied. However, little is known about these vari‑ ables’ comparative influence on the development of nascent ventures in countries with different levels of gross domestic product per capita. This research compares the effects of self‑perceptions, perceived subjective norms, and first‑hand connections with entrepreneurs on participation in nascent entrepreneurs in Latin America. Logistic regressions are performed and the resulting coefficient magnitudes and pseudo‑R2 val‑ ues compared for the populations of 11 countries in this region. The evidence reveals heterogeneity in the effect of these psychological and social attributes on nascent ventures’ creation process, conditional on different levels of gross domestic product per capita. Notably, higher economic development is positively related to a greater influence of these perceptual and social variables. The findings enhance understanding of the effects of key variables from theories of entrepreneurial behaviour, incorporat‑ ing economic development level as a new determinant. In addition, the results could guide programmes aimed at strengthening entrepreneurship in Latin America by sup‑ porting the adaptation of efforts to support nascent entrepreneurship according to the influence of perceptual and social variables in different countries.
Keywords: Social capital; Self perceptions; Nascent entrepreneurship; Social norms; Economic development